Accelerate sampling in atomistic energy landscapes using topology-based coarse-grained models - Zhang, Weihong; Chen, Jianhan (My University, 2014)
We describe a multiscale enhanced sampling (MSES) method where efficient topology-based coarse-grained models are coupled with all-atom ones to enhance the sampling of atomistic protein energy landscape. The bias from the coupling is removed by Hamiltonian replica exchange, thus allowing one to benefit simultaneously from faster transitions of coarse-grained modeling and accuracy of atomistic force fields. The method is demonstrated by calculating the conformational equilibria of several small but nontrivial β-hairpins with varied stabilities.
Keywords: Multi-Scale; Enhanced Sampling; Implicit Solvent; Protein Folding; Replica Exchange; Conformational Ensemble; Hairpin